What Are the Emerging Trends, Research Gaps, and Future Directions of Personalized Care in Nursing? - Pranata, Satriya; Shu-Fang Vivienne Wu; Shu-Yuan Liang; Yeu Hui Chuang (Journal of Applied Nursing and Health, 2026)
Background: Trends show that research on personalized care continues to increase annually. In future studies, researchers need information on trends and innovations to inform personalized care research. The purpose of the study was to explore the trend of the number of publications, the trend of the number of citations, the journal with the highest number of publications, which field has the most consent to publish, network visualization, overlay visualization, and density visualization on the topic of personalized care through bibliometric analysis. Methods: This study qualifies as a bibliometric analysis. Papers in this study are restricted to those published from 2021 to 2026, with a focus on the fields of health sciences and nursing, and on publication types. The data sources used in this study are based on online searches via https://app.dimensions.ai/. Data was collected in January 2026. Researchers analyse the data using VOS viewer. Results: Research on personalized care began to increase in 2021, peaking in 2025. Through this study, we identified that the use of artificial intelligence can achieve the goal of personalizing patient needs. Numerous studies have been conducted on the development of artificial intelligence in nursing, but they are still limited to systematic reviews, scoping reviews, literature reviews, and meta-analyses. Moreover, the system surrounding the patient to achieve personalization comprises family, caregivers, health workers, and the patient. The tendency of which diseases are most often developed and discussed in the personalized care approaches is cancer (lung cancer and breast cancer), chronic diseases (diabetes, heart disease, and kidney disease), with cancer being the most frequently discussed topic. The focus of personalized care interventions across various diseases is on exercise, diet, medication adherence, and chemotherapy. Overall, personalization is expected to reduce levels of anxiety, fatigue, complications, and depression, as well as improve the quality of life of each patient. On the other hand, the least frequently discussed topics in personalized care are patients with mental disorders, dementia, cancer, self-care, and spiritual care. Conclusion: Personalized care emphasizes not only the use of artificial intelligence and genetic technology to identify each patient's individual needs but also considers patient preferences and health profiles. Personalized care is a challenge that must be addressed to improve patient satisfaction with healthcare services in the future.